The impact of transcription on metabolism in prostate and breast cancers - Poulose, N; Mills, I; Steele, R (Bioscientifica, 2018)
Metabolic dysregulation is regarded as an important driver in cancer development and progression. The impact of transcriptional changes on metabolism has been intensively studied in hormone-dependent cancers, and in particular, in prostate and breast cancer. These cancers have strong similarities in the function of important transcriptional drivers, such as the oestrogen and androgen receptors, at the level of dietary risk and epidemiology, genetics and therapeutically. In this review, we will focus on the function of these nuclear hormone receptors and their downstream impact on metabolism, with a particular focus on lipid metabolism. We go on to discuss how lipid metabolism remains dysregulated as the cancers progress. We conclude by discussing the opportunities that this presents for drug repurposing, imaging and the development and testing of new therapeutics and treatment combinations.